Clinical experience with the WIOL-CF accommodative bioanalogic intraocular lens: Czech national observational registry - Studeny, Pavel; Krizova, Deli; Urminsky, Juraj (European journal of ophthalmology, 2016)
PURPOSE: To assess efficacy and patient satisfaction after cataract surgery and implantation of a new accommodative bioanalogic intraocular lens (IOL). METHODS: We evaluated the collected data of 48 patients with bilateral cataract surgery and Wichterle IOL (WIOL) implantation included in the Czech national observational registry. Monocular and binocular uncorrected distance visual acuity (UDVA), uncorrected intermediate visual acuity, uncorrected near visual acuity (UNVA), best spectacle-corrected visual acuity for distance (CDVA), best spectacle-corrected visual acuity for near (CNVA), distance-corrected near visual acuity (DCNVA), and distance-corrected intermediate visual acuity were evaluated 6 months after surgery. Subjective patient satisfaction was assessed at 3 months postoperatively. RESULTS: The mean monocular UDVA was 0.074 ± 0.108 logMAR, the mean monocular CDVA was 0.047 ± 0.125 logMAR, the mean monocular UNVA was 0.328 ± 0.146 logMAR, the mean monocular DCNVA was 0.339 ± 0.131 logMAR, and the mean monocular CNVA was 0.139 ± 0.107 logMAR. A total of 24 patients (50%) had no problems with any light phenomena. A total of 18 patients were very satisfied (37.5%), 11 were satisfied (22.9%), 15 (31.2%) were rather satisfied, 4 (8.3%) were rather dissatisfied, and 0 were dissatisfied. CONCLUSIONS: The WIOL-continuous focus polyfocal lens offers very good vision at far and intermediate distance comparable with other types of multifocal IOLs, and relatively good near vision, while the incidence of adverse side phenomena is relatively low.
Keywords: spokojenost pacientů; Female; nitrooční čočky; Prosthesis Design; Patient Satisfaction; protézy - design; ženské pohlaví; fakoemulzifikace; Eyeglasses; Accommodation, Ocular; Registries; lidé; Phacoemulsification; Aged, 80 and over; Lenses, Intraocular; Vision, Binocular; Male; akomodace oka; Aged; Czech Republic; pseudofakie; brýle; Pseudophakia; Lens Implantation, Intraocular; Česká republika; lidé středního věku; registrace; senioři nad 80 let; vidění binokulární; senioři; mužské pohlaví; implantace nitrooční čočky; zraková ostrost; Visual Acuity; Middle Aged; Humans